The Mediating Effect of Innovation in Between Strategic Orientation and Enterprise Performance: Evidence From Malaysian Manufacturing Small-to-Medium-Sized Enterprises - Al Mamun, Abdullah; Hayat, Naeem; Fazal, Syed Ali; Salameh, Anas A.; Zainol, Noor Raihani; Makhbul, Zafir Khan Mohamed (Frontiers in Psychology, 2022)
Strategic orientation and innovation are vital determinants for accelerating the performance of small to medium-sized enterprises (SMEs). However, there is a lack of empirical evidence confirming the innovation at the product and process level of innovation instigating the SMEs' performance. Moreover, the mediating effect of process and product innovation can play a significant role in strategic orientation and manufacturing SMEs' performance. In this respect, the present study aims to examine the mediating effect of product and process innovation between strategic orientation (i.e., market, entrepreneurial, and customer orientation) and the performance of Malaysian manufacturing SMEs. The questionnaire survey gathered data from 360 manufacturing SMEs and analyzed employing partial least square structural equation modelling (PLS-SEM) to achieve these research objectives. The study analysis established that customer and entrepreneurial orientation significantly influence product and service innovation. However, the market orientation is significant for process innovation but insignificant for product-level innovation among SMEs. The study consequences exposed that process innovation has significantly mediated between the strategic (market, customer, and entrepreneurial) orientation and SME performance. It implies that market, entrepreneurial, and customer-related strategies would substantially improve SMEs' performance by harnessing innovation's product and process levels. The core insights provided by the current work are to strengthen the strategic orientation that can promote product and process innovation, harnessing the SMEs' performance. Additionally, the study's significance and limitations were reported at the end.